2021
DOI: 10.1002/ptr.7275
|View full text |Cite
|
Sign up to set email alerts
|

From plants to antimicrobials: Natural products against bacterial membranes

Abstract: Bacterial membrane barrier provides a cytoplasmic environment for organelles of bacteria. The membrane is composed of lipid compounds containing phosphatide protein and a minimal amount of sugars, and is responsible for intercellular transfers of chemicals. Several antimicrobials have been found that affect bacterial cytoplasmic membranes. These compounds generally disrupt the organization of the membrane or perforate it. By destroying the membrane, the drugs can permeate and replace the effective macromolecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 224 publications
2
20
0
Order By: Relevance
“…ribose, Na glutamate) but they also interfere with membrane functions (electron transport, nutrient uptake, protein, nucleic acid synthesis and enzyme activity) [ 33 ]. Thus, active phenolic compounds might have several invasive targets which could lead to the inhibition of bacterial pathogens [ 33 , 34 ]. There was a study that found the ginger leaves and chia seeds with higher phenolic content showed more significant potential to eliminate the pathogenic bacteria [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…ribose, Na glutamate) but they also interfere with membrane functions (electron transport, nutrient uptake, protein, nucleic acid synthesis and enzyme activity) [ 33 ]. Thus, active phenolic compounds might have several invasive targets which could lead to the inhibition of bacterial pathogens [ 33 , 34 ]. There was a study that found the ginger leaves and chia seeds with higher phenolic content showed more significant potential to eliminate the pathogenic bacteria [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the global focus is on the study of bioactive natural regulators for human health. This seems to be more important in modern times, because a diet-dependent preventive lifestyle may reduce our growing dependence on antibiotics or may combine to increase the efficacy of antibiotics ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of bacterial membranes or alteration of permeability can lead to the production of intracellular ROS and leakage of the intracellular material. Given the membrane-targeting properties of compounds III5 and III15 , we, therefore, determined the effects of III5 and III15 on the production of intracellular ROS and leakage of bacterial proteins and DNA. The marked accumulation of intracellular ROS was in a dose-dependent manner (Figure S2) when MRSA was treated with III5 and III15 , and III15 exhibited a stronger effect of inducing ROS production compared with III5 .…”
Section: Resultsmentioning
confidence: 99%